Bioefficacy Determination of Methionine Hydroxy Analog-Free Acid Relative to DL-Methionine in Laying Hen Diets with Limited Methionine Using Different Regression Models - Bateman, Andrew; Liu, Zhenhua; Sr., David A. Roland (International Journal of Poultry Science, 2005)
A study was conducted to compare bioefficacy of liquid DL-methionine hydroxy analogue-free acid (MHA-FA) and DL-methionine (DL-Met) in laying hens. Biological efficacy was determined for egg production, egg mass, and egg weight using five regression models. Four levels of DL-Met (0.012, 0.024, 0.036, and 0.048%) and MHA-FA (0.014, 0.027, 0.041, and 0.054%) were added on an equimolar basis to a basal diet containing 14.97% protein and 0.27% methionine. Twenty week old Hy-Line W-36 hens were used in this trial with 8 replicates per treatment. The bioefficacy of MHA-FA related to DL-Met was 0.77 on a weight basis (or 0.87 on a molar basis) based on egg mass with the best goodness of model fit (average R2 equal to 83.33%). The bioefficacy was 0.71 on a weight basis (or 0.80 on a molar basis) based on egg production with the goodness of model fit at average R2 equal to 76.98%. The bioefficacy was 1.03 on a weight basis (or 1.17 on a molar basis) based on egg weight with the goodness of model fit at average R2 equal to 68.83%.